Morning Prayer : on the importance of practice [a question without answer] and contact [an unfulfilled desire] - Bonnefantenmuseum, Maastricht (Maastricht : Bonnefantenmuseum, 2012)
Alecu, Adrian; Borress, Clifford; Lemaitre, Christophe; Mihaylova, Snejanka; Rubin, Nathania; Valk, Esmé
Published on the occasion of the exhibition "Theatre of Thought" (named after the book by Snejanka Mihaylova) at the Bonnefantenmuseum in Maastricht, 02.10.2012 - 27.01.2013
boek